Discrimination of Hemorrhage and Contrast Media in a Head Phantom on Photon-Counting Detector CT Data - Risch, Franka; Berlis, Ansgar; Kroencke, Thomas; Schwarz, Florian; Maurer, Christoph J. (American Journal of Neuroradiology, 2024)
In this anthropomorphic head phantom study, samples containing blood and contrast agent with concentrations ranging from 0 to 6 mg iodine per milliliter and another set of samples without blood for reference were scanned with a photon-counting detector CT using a standard cranial protocol. It was demonstrated that photon-counting detector CT can reliably distinguish hemorrhage and contrast media, including density determination of the latter. The technology promises to add value in several neuroimaging applications.CMcontrast mediaME70virtual monoenergetic image at 70 keVPCDphoton-counting detectorVNCvirtual noncontrast